Assessing Accuracy and Reliability : A Note Basedon Approaches Used in National Accounts and Balance of Payments Statistics - Carson, Carol; Laliberte, Lucie (Washington, D.C. : International Monetary Fund, 2002)
Both national accounts and balance of payments are based on multiple, complex source data and typically undergo several routine revisions as more and better source data are incorporated into the final estimates. As a result, neither dataset can be subjected directly to the usual statistical measures of sampling biases, variances, and other measurement error properties. In this context, this note, which is addressed to those interested in these datasets and others, explores four approaches that shed light on the accuracy and reliability of these datasets: examination of statistical discrepancies, comparison with other data, analysis of revisions, and judgmental evaluation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet